Subspecies and Distribution. L.s.sibiricusKerr,1792—NEEuropeanRussia,NovayaZemlya,andW&CSiberiaasfarEasLenaRiver. L.s.bunge:Vinogradov,1925—ESiberiabetweenLenaandKolymarivers. L.s.novosibiricusVinogradov,1925—NewSiberianIs(NERussia). L. s. portenkoi Tschernyavsky, 1967 — Wrangel I (NE Russia). in Cricetidae ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Subspecies and Distribution. L.s.sibiricusKerr,1792—NEEuropeanRussia,NovayaZemlya,andW&CSiberiaasfarEasLenaRiver. L.s.bunge:Vinogradov,1925—ESiberiabetweenLenaandKolymarivers. L.s.novosibiricusVinogradov,1925—NewSiberianIs(NERussia). L. s. portenkoi Tschernyavsky, 1967 — Wrangel I (NE Russia). ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 293, DOI: 10.5281/zenodo.6707142 ...